2023
DOI: 10.1021/acs.orglett.3c02358
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanides as Acceptor Groups in MHAT Reactions with Unactivated Alkenes

Jordi Puig,
Josep Bonjoch,
Ben Bradshaw

Abstract: The use of isocyanides as acceptor groups in metal–hydride hydrogen atom transfer (MHAT) coupling reactions with nonactivated alkenes to form heterocycles is described. Monosubstituted alkenes couple and cyclize directly, whereas more substituted alkenes proceed via a two-step, one-pot procedure involving MHAT reductive cyclization followed by a MHAT Minisci coupling upon the addition of acid. To highlight the utility of the methodology, a diverse variety of substituted heterocycles such as phenanthridines, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Further investigation revealed that the types of supporting electrolytes also significantly affected the reaction efficiency ( [20][21][22][23][24][25]. Decreasing of the current density from 17.3 mA cm À 2 to 13.5 and 9.6 mA cm À 2 or increasing it to 23.1, 30.8, 38.5 and 57.7 mA cm À 2 afforded 2 a in modest to low yields (Table 1, entries [26][27][28][29][30][31]. Slightly lower yield was observed when the reaction temperature was raised to 80 °C (Table 1, entry 32).…”
Section: Resultsmentioning
confidence: 99%
“…Further investigation revealed that the types of supporting electrolytes also significantly affected the reaction efficiency ( [20][21][22][23][24][25]. Decreasing of the current density from 17.3 mA cm À 2 to 13.5 and 9.6 mA cm À 2 or increasing it to 23.1, 30.8, 38.5 and 57.7 mA cm À 2 afforded 2 a in modest to low yields (Table 1, entries [26][27][28][29][30][31]. Slightly lower yield was observed when the reaction temperature was raised to 80 °C (Table 1, entry 32).…”
Section: Resultsmentioning
confidence: 99%
“…This radical-based approach has been extensively used in the synthesis of polycyclic frameworks and the total synthesis of complex natural molecules . Along with this, a plethora of electron-deficient acceptors have been employed in the MHAT reactions to form C–C bonds for the synthesis of cyclic, as well as acyclic, scaffolds . However, there are only a handful of strategies reported for the synthesis of substituted heterocycles using MHAT reactions.…”
mentioning
confidence: 99%
“…Isocyano compounds are versatile building blocks to produce functionalized nitro-containing molecules. , Specifically, the radical-type coupling/cyclization of 2-isocyanobiaryls enabled a number of robust methods for the synthesis of phenanthridines . Bradshaw and co-workers discovered the iron-catalyzed metal hydride hydrogen atom transfer (MHAT) to realize formally redox-neutral self-cyclization of 2-isocyanobiphenyl, where stoichiometric amounts of both reductant (PhSiH 3 ) and oxidant (TBHP) were required to achieve the catalytic cycle; however, the dual use of oxidant and reductant greatly limits its application (Figure a).…”
mentioning
confidence: 99%